A Novel High‐Performance TiO2‐x/TiO1‐yNy Coating Material for Silicon Anode in Lithium‐Ion Batteries. Issue 7 (26th May 2022) - Wang, Sung Eun; Kim, Min Ji; Lee, Jin Woong; Chun, Jinyoung; Choi, Junghyun; Roh, Kwang Chul; Kang, Yun Chan; Jung, Dae Soo
Abstract: Protective surface coatings on Si anodes are promising for improving the electrochemical performance of lithium‐ion batteries (LIBs). Nevertheless, most coating materials have severe issues, including low initial coulombic efficiency, structural fracture, morphology control, and complicated synthetic processing. In this study, a multifunctional TiO2‐ x /TiO1‐ y N y (TTN) formed via a facile and scalable synthetic process is applied as a coating material for Si anodes. A thin layer of amorphous TiO2 is uniformly coated onto Si nanoparticles by a simple sol–gel method and then converted into a two phase TiO2‐ x /TiO1‐ y N y via nitridation. The lithiated TiO2‐x provides high ionic and electrical conductivity, while TiO1‐y Ny can improve mechanical strength that alleviates volume change of Si to address capacity fading issue. Owing to these synergetic advantages, TiO2‐ x /TiO1‐ y N y ‐coated Si (Si@TTN) exhibits excellent electrochemical properties, including a high charge capacity of 1650 mA h g –1 at 0.1 A g –1 and 84% capacity retention after 100 cycles at 1 A g –1 . Moreover, a significantly enhanced rate performance can be achieved at a high current density. This investigation presents a facile and effective coating material to use as the high‐capacity silicon anode in the emerging Si anode technology in LIBs. Abstract : A novel TiO2‐x /TiO1‐y Ny material is fabricated as a coating material for silicon nanoparticle anodes. Core–shell structured Si@TiO2‐x /TiO1‐y Ny composite is obtained by a scalable sol–gel approach and applied as an anode for lithium‐ion batteries. The synergistic effect of TiO2‐x and TiO1‐y Ny providing ionic/electrical pathways and mechanical robustness, respectively, results in high structural stability and rate capability.